Modeling and using context : 11th International and Interdisciplinary Conference, CONTEXT 2019, Trento, Italy, November 20-22, 2019, Proceedings /: 11th International and Interdisciplinary Conference, CONTEXT 2019, Trento, Italy, November 20-22, 2019, Proceedings. (2019) - Unknown
No abstract available